Preliminary Conclusions Following Archaeological-Anthropological Studies in the Crypts of the Church of Saint John the Baptist and the Five Martyred Brothers in Kazimierz Biskupi, Kazimierz Biskupi Commune, Konin County, Greater Poland Province (2022 Season) - Grupa, Małgorzata; Pawlak, Piotr; Dryjański, Waldemar; Grupa, Dawid; Kozłowski, Tomasz; Nowosad, Wiesław (Analecta Archaeologica Ressoviensia, 2024)
The studies conducted in the crypts in the Church of Saint John Baptist and the Five Martyred Brothers in 2022 allowed for the strata that have accumulated in specific features over the course of more than 200 years to be explored. The analysis of archaeological-anthropological and archival materials showed numerous inconsistencies that arose at the time when the crypts were being ordered and have neither been accounted for nor corrected in the Bernardine chronicles. This information along with other data obtained in the course of the conservation procedures provides a different take on the history of the church and the funeral and material culture in the modern era and the period of the Partitions of Poland.